Effect of the ring size of TMC ligands in controlling C–H bond activation by metal-superoxo species. Issue 15 (29th March 2022) - Monika,; Ansari, Azaj
Abstract : This work is based on deep insight into the role of the ring size of ligands during C–H bond activation. Our findings can help design catalysts with better catalytic reactions. Abstract : Metal-superoxo species play a very important role in many metal-mediated catalytic transformation reactions. Their catalytic reactivity is affected by many factors such as the nature of metal ions and ring size of ligands. Herein, for the first time, we report DFT calculations on the electronic structures of a series of metal-superoxo species (M = V, Cr, Mn, Fe, and Co) with two ring size ligands, i.e., 13-TMC/14-TMC, and a detailed mechanistic study on the C–H bond activation of cyclohexa-1, 4-diene followed by the effect of the ring size of ligands. Our DFT results showed that the electron density at the distal oxygen plays an important role in C–H bond activation. By computing the energetics of C–H bond activation and mapping the potential energy surface, it was found that the initial hydrogen abstraction is the rate-determining step with both TMC rings and all the studied metal-superoxo species. The significant electron density at the cyclohex-1, 4-diene carbon indicates that the reaction proceeds via the proton-coupled electron transfer mechanism. By mapping the potential energy surfaces, we found that the 13-TMC ligated superoxo with the anti-isomer are more reactive than the 14-TMC superoxo species except for the iron-superoxo species where the 14-TMC ligated superoxo species is more reactive i.e. smaller ring size TMC is more reactive towards C–H bond activation. This is also supported by the structural correlation, i.e., the greater contraction in the smaller ring results in the metal being pushed out of plane along the z -axis, which reduces the steric hindrance. Thus, the ring size can help in designing catalysts with better efficiency for catalytic reactions.